Determinant of Fraud Detection on Financial Statement - Muhammad Nur Deni Musa; Rahma Satya Masna Hatuwe; Saling Saling; La Ode Marihi (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2022)
This study was a replication of conceptual model of empirical studies aimed to analyze the effect of professional skepticisms, auditor experience, competency, independence and time pressure on the fraud detection of financial statement. The result of this study was expected to be able reducing the gap among the so many empirical studies existing. This study could be categorized as explanatory research. The samples in this study were all the auditors in BPKP Maluku and Papua consisting of 88 auditors. The analysis tool used was multiple linear regression analysis with questionnaire instrument as data collection instrument. The result of this study showed that; professional skepticism and auditors experience hand significant impact on the author ability in detecting fraud on financial statement, competence and independence of auditors had not significant effect on the auditors ability in detecting fraud and time pressure affected the auditors ability in detecting fraud but it was not significant.